2018
DOI: 10.1007/s11103-018-0747-4
|View full text |Cite
|
Sign up to set email alerts
|

An armadillo-domain protein participates in a telomerase interaction network

Abstract: Arabidopsis and human ARM protein interact with telomerase. Deregulated mRNA levels of DNA repair and ribosomal protein genes in an Arabidopsis arm mutant suggest non-telomeric ARM function. The human homolog ARMC6 interacts with hTRF2. Telomerase maintains telomeres and has proposed non-telomeric functions. We previously identified interaction of the C-terminal domain of Arabidopsis telomerase reverse transcriptase (AtTERT) with an armadillo/β-catenin-like repeat (ARM) containing protein. Here we explore prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
0
15
0
2
Order By: Relevance
“…Homologues of the mammalian Pontin and Reptin, named RuvBL proteins, as well as TRB proteins, might be involved in diverse processes in the plant cell. AtTRB proteins are not only components of terminal complex associated with telomeres and catalytic subunit of telomerase, AtTERT (Schrumpfová et al ., , ), but they also serve as epigenetic regulators that potentially impact the transcription status of thousands of genes as subunits of epigenetically active multiprotein complexes (Lee and Cho, ; Schrumpfová et al ., ; Zhou et al ., ; Dokládal et al ., ; Tan et al ., ). AtRuvBL1 protein has been assumed as a regulator of R genes so far and is essential in meristem development (Holt et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Homologues of the mammalian Pontin and Reptin, named RuvBL proteins, as well as TRB proteins, might be involved in diverse processes in the plant cell. AtTRB proteins are not only components of terminal complex associated with telomeres and catalytic subunit of telomerase, AtTERT (Schrumpfová et al ., , ), but they also serve as epigenetic regulators that potentially impact the transcription status of thousands of genes as subunits of epigenetically active multiprotein complexes (Lee and Cho, ; Schrumpfová et al ., ; Zhou et al ., ; Dokládal et al ., ; Tan et al ., ). AtRuvBL1 protein has been assumed as a regulator of R genes so far and is essential in meristem development (Holt et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…In plants, the armadillo/β-catenin-like repeat-containing protein (ARM) or Chromatin remodeling 19 (CHR19) proteins associated with TERT may reflect the possible non-telomeric functions of telomerase [167]. ARM proteins play a role in the Wnt/β-catenin signaling pathway in humans [168], but the non-telomeric functions of plant TERT or TR remain elusive.…”
Section: D) Association With Telomerementioning
confidence: 99%
“…TRB proteins are not only components of the terminal complex associated with telomeres/telomerase, but they are also associated in vivo with promoters of translation machinery genes, which mostly contain a short telomeric sequence [67]. It seems that TRB proteins serve as epigenetic regulators that potentially affect the transcription status of thousands of genes by playing a role of recruiting subunits of multiple epigenetically active multi-protein complexes [68,69,70,71,155,156]. These findings are consistent with the observations from yeast or mammals where telomeric proteins (e.g., TRF1, TRF2, and RAP1) are able to localize outside telomeric regions and regulate the transcription of genes involved in metabolism, immunity, and differentiation [157,158,159,160,161,162,163,164].…”
Section: Telomere Chromatin Compositionmentioning
confidence: 99%
“…Surprisingly, no functions in telomere maintenance were found in Arabidopsis orthologues of mammalian TRF proteins (TRFL proteins) where a myb-domain of the telobox type is located C-terminally as in human TRF1 and TRF2 [165]. However, a recent study revealed protein-protein interactions between TRFL2 and TRP1, members of the TRFL family, and TERT from A. thaliana [66,69]. Plant TRFL2 and TRP1 proteins interact with armadillo/β-catenin-like repeat-containing protein (ARM).…”
Section: Telomere Chromatin Compositionmentioning
confidence: 99%
See 1 more Smart Citation